Purple basil: Nutritional attributes, biological activities, bioactive compounds and food applications - Ozcan, Basak Ebru; Kosar, Maide; Uluata, Sibel; Karadag, Ayse (ELSEVIER, 2026)
This review aims to provide updated and critical scientific insights into the nutraceutical properties, detailed nutritional composition, and bioactive constituents of purple basil (Ocimum basilicum L.), along with its potential applications in food product development. Highlighting its significance as an edible herb, purple basil exhibits diverse therapeutic properties, including antioxidant, antimicrobial, antidiabetic, anticancer, and antiinflammatory effects. It is a rich source of bioactive compounds such as monoterpenes, phenolic acids, and flavonoids, with anthocyanins (ACNs) being the predominant pigments responsible for its red and purple hues. Key volatile constituents include linalool, 1,8-cineole, methyl cinnamate, and methyl chavicol, while rosmarinic acid, caftaric acid, and chicoric acid represent the major phenolic acids. Extracts of purple basil, owing to their high ACN content, have also been explored as natural pH-sensitive indicators. Despite the extensive documentation of its bioactive potential, further research is needed to elucidate the health effects, bioavailability and toxicity of purple basil extracts.
Keywords: Anthocyanins; Peonidin; Rosmarinic acid; Chicoric acid; Essential oil; OCIMUM-BASILICUM; ESSENTIAL-OIL; ANTIOXIDANT PROPERTIES; ANTIBACTERIAL ACTIVITY; PHENOLIC COMPOSITION; L. LEAF; EXTRACTION; GREEN; OPTIMIZATION; Food Science & Technology